2019
DOI: 10.1016/j.cgh.2018.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance vs Transient Elastography Analysis of Patients With Nonalcoholic Fatty Liver Disease: A Systematic Review and Pooled Analysis of Individual Participants

Abstract: In a pooled analysis of data from individual participants with biopsy-proven NAFLD, we found MRE to have a statistically significantly higher diagnostic accuracy than TE in detection of each stage of fibrosis. MRE and TE each have roles in detection of fibrosis in patients with NAFLD, depending upon the level of accuracy desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
266
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 288 publications
(297 citation statements)
references
References 43 publications
2
266
1
4
Order By: Relevance
“…VCTE is inexpensive and can be measured in the clinic but has inferior diagnostic performance in head-to-head comparison studies with MRE, particularly for lower stages of fibrosis and in the morbidly obese. (12)(13)(14) In contrast to liver biopsy, MRE evaluates a much larger volume of the total liver (~5%), is reproducible, (15) and has high interobserver agreement. (16) While cross-sectional studies have demonstrated that MRE has superior diagnostic performance in NAFLD, there are limited longitudinal data on the association between changes in MRE and liver fibrosis on paired liver biopsies.…”
Section: Clinical Utility Of An Increase In Magnetic Resonance Elastomentioning
confidence: 99%
“…VCTE is inexpensive and can be measured in the clinic but has inferior diagnostic performance in head-to-head comparison studies with MRE, particularly for lower stages of fibrosis and in the morbidly obese. (12)(13)(14) In contrast to liver biopsy, MRE evaluates a much larger volume of the total liver (~5%), is reproducible, (15) and has high interobserver agreement. (16) While cross-sectional studies have demonstrated that MRE has superior diagnostic performance in NAFLD, there are limited longitudinal data on the association between changes in MRE and liver fibrosis on paired liver biopsies.…”
Section: Clinical Utility Of An Increase In Magnetic Resonance Elastomentioning
confidence: 99%
“…While these results are comparable to ALT/AST ratio or the NFS in other published cohorts, the substitution of ALT and AST with a marker that more closely correlates with extracellular matrix turnover is likely to produce more robust results over different cohorts and countries. Still, these results are below the accuracy of modern imaging‐based biomarkers, albeit similar to an AUROC of 0.83 using vibration‐controlled elastography (VCTE) but a significantly higher AUROC of 0.93 using magnetic resonance elastography (MRE) for detection of stage 3 and stage 4 fibrosis in NAFLD . A head‐to‐head comparison as well as a combination approach with ADAPT, VCTE, and the enhanced liver fibrosis panel will be helpful in assessing if one could achieve an AUROC similar to MRE.…”
mentioning
confidence: 96%
“…1,3 Additionally, we were able to determine among this large general, average-risk population (excluding current and past viral hepatitis, significant alcohol use, and those with high ALT values), the mean ± SD for a 'normal' liver stiffness value when using MRE (2.4 ± 0.3 kPa), a critical value that has been hindered by small sample sizes or the use of highly selected populations. [4][5][6][7] This finding may now help assist policy decision makers determine an accurate cut-off point to determine normal liver stiffness.…”
Section: Editorsmentioning
confidence: 81%